Polychlorinated biphenyl (PCB) concentrations and profiles in marine mammals from the North Atlantic Ocean. (February 2022) - Megson, David; Brown, Thomas; Jones, Gareth Rhys; Robson, Mathew; Johnson, Glenn W.; Tiktak, Guuske P.; Sandau, Courtney D.; Reiner, Eric J.
Abstract: Polychlorinated biphenyls (PCBs) can provide crucial information into the bioaccumulation and biomagnification of POPs in marine mammals. Muscle tissue samples were obtained for detailed PCB congener specific analysis of all 209 PCBs in 11 species of marine mammals stranded across the coast of the UK between 2010 and 2013. At least 145 PCB congeners were found in each individual. The highest concentrations of PCBs were recorded in a killer whale (318 mg/kg lipid) and the highest toxic equivalent in a Risso's dolphin (1687 pg/g TEQ2005 wet). Concentrations of PCBs in the majority of samples exceeded toxic thresholds (9 mg/kg lipid) for marine mammals, highlighting the health risk they face from PCB exposure. Many PCB profiles did not fit typical 'Aroclor' signatures, but instead indicated patterns of congeners that are resistant to biotransformation and elimination. However, this study identified a novel PCB signature in a sei whale that has not yet been previously observed in marine mammals. The whale had a PCB profile that included lighter and inadvertent PCB congeners such as PCB 11, suggesting that the main source of exposure was through atmospheric deposition, rather than terrestrial discharges. Seven subsamples were chosen for chiral analysis of PCB 95, 136 and 149. The enantiomer fractions (EFs) of C-PCBs 95 and 149 were non racemic suggesting there may be enantiomer selective metabolism in marine mammals. Although there has been a shift in the literature towards emerging pollutants, this study acts as a stark reminder that PCBs continue to pose a significant risk to wildlife. Graphical abstract: Image 1 Highlights: Over 145 different PCBs consistently detected in samples. PCBs continue to pose a significant risk to marine mammals. Inadvertent PCBs can contribute >5% of total PCB load. Unique atmospheric deposition PCB signature identified in sei whale.